Stability of a frame-based maximal weight matching algorithm with transfer speedup - Xike Li; Elhanany, I. (IEEE communications letters, 2005)
It has been shown that maximal size matching algorithms for input-queued switches are stable under any admissible traffic conditions with a scheduling speedup of 2. However, as link speeds increase, the computational complexity of these algorithms limits their applicability in high port-density switches and routers. In this letter we describe a Frame-Based Maximal Weight Matching (FMWM) algorithm in which a new scheduling decision is issued once every several cell times. Between scheduling decisions, the configuration of the crossbar switch remains unchanged. We prove that the FMWM algorithm is stable with an internal buffer transfer speedup of 2, thereby significantly relaxing the timing constraints on the scheduling process. Simulation results illustrate the impact of the algorithm on the average cell delay for different traffic scenarios.